Manual de puestos y procedimientos - Guzmán-Berrocal, Víctor Manuel (Instituto Tecnológico de Costa Rica., 2019)
The purpose of this research is to implement a Procedures and Positions Manual for the Academic and Administrative Areas of the Instituto Nacional de la Música, an organization funded in 1997 dedicated to the musical and artistic development of its students. The research has a qualitative approach since it seeks to generate the formal documents of the INM organizational structure, this through the collection of data by the use of tools such as quistionnaire and direct observation of each collaborator. With these data, a sample of 8 positions and 17 procedures was evaluated. With the implementation of the proposed Manuals, it is intended to optimize the development of the daily activities of the INM that allows a constant and efficient business turnaround.
diseño del manual de puestos y procedimientos para el Instituto Nacional de la Música
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2019.
Keywords: Instituto Nacional de la Música; Manuales de puestos; Administración de recursos humanos